High-risk chronic lymphocytic leukemia in the era of pathway inhibitors: integrating molecular and cellular therapies - Dreger, Peter (Blood, 2018)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - High-risk chronic lymphocytic leukemia (CLL) has been defined by clinical and/or genetic resistance (TP53 abnormalities) to treatment with chemoimmunotherapy (CIT). With the availability of pathway inhibitors (PIs), such as kinase inhibitors and BCL2 antagonists, the outlook of CIT-resistant patients has dramatically improved. Here, we propose a revision of the concept of high-risk CLL, driven by TP53 abnormalities and response to treatment with PI. CLL high-risk-I, CIT-resistant is defined by clinically CIT-resistant disease with TP53 aberrations, but fully responsive to PI. This category is largely the domain of PI-based therapy, and cellular therapy (ie, allogeneic hematopoietic cell transplantation) remains an option only in selected patients with low individual procedure-related risk. In CLL high-risk-II, CIT- and PI-resistant, characterized by increasing exhaustion of pharmacological treatment possibilities, cellular therapies (including chimeric antigen receptor-engineered T cells) should be considered in patients eligible for these procedures. Moreover, molecular and cellular therapies are not mutually exclusive and could be used synergistically to exploit their full potential.
Gesehen am 14.06.2019